Charge Transfer Properties of Heterostructures Formed by Bi2O2Se and Transition Metal Dichalcogenide Monolayers. Issue 7 (3rd December 2021) - Liu, Shuangyan; He, Dawei; Tan, Congwei; Fu, Shaohua; Han, Xiuxiu; Huang, Mohan; Miao, Qing; Zhang, Xiaoxian; Wang, Yongsheng; Peng, Hailin; Zhao, Hui
Abstract: Atomically thin bismuth oxyselenide (Bi2 O2 Se) exhibits attractive properties for electronic and optoelectronic applications, such as high charge‐carrier mobility and good air stability. Recently, the development of Bi2 O2 Se‐based heterostructures have attracted enormous interests with promising prospects for diverse device applications. Although the electrical properties of Bi2 O2 Se‐based heterostructures have been widely studied, the interlayer charge transfer in these heterostructures remains elusive, despite its importance in harnessing their emergent functionalities. Here, a comprehensive experimental investigation on the interlayer charge transfer properties of two heterostructures formed by Bi2 O2 Se and representative transition metal dichalcogenides (namely, WS2 /Bi2 O2 Se and MoS2 /Bi2 O2 Se) is reported. Kelvin probe force microscopy is used to measure the work functions of the samples, which are further employed to establish type‐II band alignment of both heterostructures. Photoluminescence quenching is observed in each heterostructure, suggesting high charge transfer efficiency. Time‐resolved and layer‐selective pump–probe measurements further prove the ultrafast interlayer charge transfer processes and formation of long‐lived interlayer excitons. These results establish the feasibility of integrating 2D Bi2 O2 Se with other 2D semiconductors to fabricate heterostructures with novel charge transfer properties and provide insight for understanding the performance of optoelectronic devices based on such 2D heterostructures. Abstract : Charge transfer properties in heterostructures formed by Bi2 O2 Se and transition metal dichalcogenide (TMD) monolayers of WS2 and MoS2 are comprehensively studied. The interfacial energy band alignments of both heterostructures are established via Kelvin probe force microscopy. Transient absorption measurements further reveal efficient interlayer charge transfer and formation of the interlayer excitons.